assume a = y^2, then:
y^4 + 5y^2 - 84 = a^2 + 5a - 84
multiply to -84, add to 5: (12, -7)
(a + 12)(a - 7)=0
resub in y^2
(y^2 + 12)(y^2 - 7) = 0
y^2 + 12 = 0
y = +/- square root (-12)
y = +/- (square root 12) i
y^2 - 7 = 0
y = +/- square root 7
2007-02-02 08:09:30
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Since there is no equal sign I assume you want to factor the expression factors of the first term are Y^2
for the third term you need 2 numbers that when multiplied equal 84 but when added equal 5 also one of these must be negative because the 84 is negative. the factors 7 and 12 will work. The middle term of the given expression is positive therefore the largest of the factors must be positive.
(y^2 - 7)(y^2 + 12) are the factors.
2007-02-02 16:25:19
·
answer #2
·
answered by bignose68 4
·
0⤊
0⤋
y^4 + 5y^2 - 84 >>12 - 7 = 5 and 12x7 = -84
= y^4 + 12y^2 - 7y^2 - 84
= y^2(y^2 + 12) - 7(y^2 + 12)
= (y^2 + 12)(y^2 - 5)
2007-02-02 16:13:22
·
answer #3
·
answered by Sheen 4
·
0⤊
0⤋
(y^2-7)(y^2+12)
2007-02-02 17:22:18
·
answer #4
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
Like this:
//``//``//``
~~??~~??~~??
^^//^^//^^//
LIke my dance?
2007-02-02 16:11:53
·
answer #5
·
answered by Summer 5
·
0⤊
2⤋